Premature ventricular complexes & risk of incident stroke: The Atherosclerosis Risk In Communities (ARIC) study - Agarwal, Sunil K. (2010)
BACKGROUND: Ventricular premature complexes (PVCs) on a 2-minute electrocardiogram (ECG) are a common, largely asymptomatic finding, associated with increased risk of coronary heart disease (CHD) and death. They may reflect atherosclerosis or other pathogenic pathways that predispose to arrhythmias and stroke. METHODS/RESULTS: We conducted a prospective evaluation of the Atherosclerosis Risk In Communities Study cohort (n=14,783) of middle aged men and women to assess whether the presence of PVCs at study baseline (1987-89) influenced the risk of incident stroke through 31(st) December 2004. PVCs were seen in 6.1% of the participants at baseline, and 729 (4.9%) had incident stroke. The unadjusted cumulative proportion of incident stroke in individuals with any PVC was 6.6% compared to 4.1% in those without PVC. The unadjusted hazard ratio (HR) of incident stroke in individuals with any PVC compared to those without any PVCs was 1.71 (95% Confidence Interval (CI) 1.33, 2.20). Among individuals without hypertension and diabetes at baseline, PVCs were independently associated with incident stroke (HR: 1.72 (1.14, 2.59)). Among those with either diabetes or hypertension the presence of any PVCs did not increase the risk of stroke. The association was stronger for non-carotid embolic stroke than for thrombotic stroke and its magnitude increased with higher frequency of PVCs. CONCLUSIONS: Frequent PVCs are associated with risk of incident stroke in participants free of hypertension and diabetes. This suggests that PVCs may contribute to atrio-ventricular remodeling or may be risk marker for incident stroke, particularly embolic stroke.